Methods of Controlling Postoperative Complications after Lymphadenectomy in Patients with Breast Cancer - E. M. Bukin; A. B. Vasin; N. S. Goloshchapova; I. N. Roschin; A. E. Akimova (Креативная хирургия и онкология)
Introduction. Reducing the aggressiveness of surgical tactics is currently considered a promising trend in medicine that is widely supported due to its better safety profile. However, a large percentage of patients need more intervention. In the treatment of breast cancer, the main difficulties in postoperative management are associated with lymphatic surgery. Aim. To perform a comparative analysis of techniques for intraoperative control of lymphorrhea in patients during lymph node dissection for breast cancer in Yaroslavl Regional Oncologic Hospital. Materials and methods. Case histories of 660 patients after axillary subclavian subscapular lymphadenectomy were analyzed. In the postoperative period, patients revealed prolonged lymphorrhea. Magnifying techniques (binocular lenses, microscope) were used during the interventions to detect and isolate lymphatic vessels in 108 patients. A double coagulation technique was used to ligate the lymphatic vessels. Sufficient coagulation surface was achieved by forming suture lines of an angle greater than 90°. When performing a mastectomy, the technique was supplemented by circular bandaging of the chest. Results and discussion. Analysis of case histories showed that lymphadenectomy proved to be the main significant factor influencing lymphorrhea. Sparing techniques reduced the risk of postmastectomy syndrome. Comparing the study group with the control group revealed a statistically significant reduction in the severity of lymphorrhea without an increase in the risk of other complications. Conclusion. The combination of these techniques demonstrated statistically significant advantages in controlling postoperative complications. The techniques are easy to perform, therefore, they can be introduced into practice with minimal costs. The economic benefits are associated with the absence of additional costs for surgery, as well as with a reduction in the duration of hospital stay for patients. All this significantly increases patient satisfaction with the treatment performed.